A transmission problem for the Timoshenko system - Raposo, C.A.; Bastos, W.D. [UNESP]; Santos, M.L. (Sociedade Brasileira de Matemática Aplicada e Computacional, 2007)
In this work we study a transmission problem for the model of beams developed by S.P. Timoshenko [10]. We consider the case of mixed material, that is, a part of the beam has friction and the other is purely elastic. We show that for this type of material, the dissipation produced by the frictional part is strong enough to produce exponential decay of the solution, no matter how small is its size. We use the method of energy to prove exponential decay for the solution.
Keywords: transmission; Timoshenko; beams; exponential decay; frictional damping